The Difference in Sibling Birthweight and Neonatal Death: A Population-Based Cohort Study - Tabet, Maya; Flick, Louise H.; Xian, Hong; Chang, Jen Jen (American Journal of Perinatology, 2019)
Background There has been a call for customized rather than population-based birthweight standards that would classify smallness based on an infant's own growth potential. Thus, this study aimed to examine the association between the difference in sibling birthweight and the likelihood of neonatal death among second births in a U.S. population.Study Design This was a population-based cohort study including 179,300 women who delivered their first two nonanomalous singleton live births in Missouri (1989–2005). We performed binary logistic regression to evaluate the association between being relatively smaller than the elder full- or half-sibling (i.e., smaller by at least 500 g) and neonatal death (i.e., deaths in the first 28 days of life) among second births after controlling for sociodemographic and pregnancy-related variables in the second pregnancy.Results The adjusted odds of neonatal death were 2.54-times higher among second births who were relatively smaller than their elder sibling. Among relatively small second births, every 100-g increase in the difference in sibling birthweight was associated with a 13% increase in the odds of neonatal death.Conclusion The deviation from the elder sibling's birthweight predicts neonatal death. Taking into consideration the elder sibling's birthweight may be warranted in clinical and research settings.
Keywords: birthweight; Missouri; neonatal death; sibling data